Aplikasi Kamus Android Indonesia-Jawa - Faisal Rahutomo; Yoppy Yunhasnawa; Agustaf Fanisnaini Narolis; Muhammad Rifky Prayanta (Prosiding SISFOTEK, 2018)
Indonesia is a rich country of culture and language. Sometimes the citizen migrates inside the country for job or education reasons. The newcomer from one region to the other region usually need to know the local language, especially Javanese, because of so many universities in the region. Therefore, this paper describes the effort to develop an android dictionary application of Indonesian-Javanese. Mobile application android is chosen in this proposal because of its popularity among Indonesian. Several features are embedded in the application, with all of the Javanese language levels. The application has the ability to recognize the voice and generate the pronunciation sound. The application is able to work both online and offline. Questionnaire results show 80% of users agree with the user interface, 60% say the application is easy to use, and 65% say of its usefulness.